Effect of recycled waste glass on the properties of high-performance concrete : A critical review - Hamada, Hussein Mahmood; Alattar, Alyaa; Tayeh, Bassam A.; Fadzil, Mat Yahaya; Skariah Thomas, Blessen (Elsevier Ltd, 2022)
Solid waste disposal is one of the major environmental concerns. Disposal of waste glass into open areas and landfills is one of the major threats that pollutes the environment in addition to the cases of health hazards around the world. Recycling the discarded glass as a sustainable construction material have received an increasing attention in the construction industry as it may mitigate the greenhouse emissions and potential environmental risks. This paper presents a brief review on the fresh, mechanical and durability properties of normal and high-performance concrete containing waste glass aggregates (WGA). The size, type, replacement ratio of the WGA, in addition to the mixing and curing methods of concrete significantly affects the mechanical and durability characteristics. The concrete containing powdered glass exhibited superior durability properties on account of the refined pore structure and densified microstructure. The findings exhibited that waste glass can be potentially utilised as coarse and fine aggregates in concrete production, along with the advanced recommendations for further studies.